2017
DOI: 10.12688/wellcomeopenres.12523.1
|View full text |Cite
|
Sign up to set email alerts
|

Supporting surveillance capacity for antimicrobial resistance: Laboratory capacity strengthening for drug resistant infections in low and middle income countries

Abstract: Development of antimicrobial resistance (AMR) threatens our ability to treat common and life threatening infections. Identifying the emergence of AMR requires strengthening of surveillance for AMR, particularly in low and middle-income countries (LMICs) where the burden of infection is highest and health systems are least able to respond. This work aimed, through a combination of desk-based investigation, discussion with colleagues worldwide, and visits to three contrasting countries (Ethiopia, Malawi and Viet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 8 publications
2
55
0
Order By: Relevance
“…2 In addition, AMR puts a financial burden on resource-limited countries. 3 Studies from East Africa have reported high levels of AMR to commonly used antibiotics with Gram-negatives showing 50% – 100% resistance to ampicillin and trimethoprim or sulfamethoxazole (for instance in Uganda, 100% resistance in Escherichia coli has been observed). The extent and burden of this resistance, however, is not being monitored through established ongoing surveillance systems.…”
Section: Introductionmentioning
confidence: 99%
“…2 In addition, AMR puts a financial burden on resource-limited countries. 3 Studies from East Africa have reported high levels of AMR to commonly used antibiotics with Gram-negatives showing 50% – 100% resistance to ampicillin and trimethoprim or sulfamethoxazole (for instance in Uganda, 100% resistance in Escherichia coli has been observed). The extent and burden of this resistance, however, is not being monitored through established ongoing surveillance systems.…”
Section: Introductionmentioning
confidence: 99%
“…These were critically assessed according to the context they were designed for, and their relevance to AMR surveillance in low and middle income countries. Concurrently, we reviewed AMR surveillance systems and existing AMR surveillance capacity 7 .…”
Section: Methodsmentioning
confidence: 99%
“…At the moment, estimates of the AMR burden in LMICs is derived through a series of extrapolations—for example the proportion of neonatal sepsis deaths attributable to drug resistant infection, estimated as 214,500 in 2012, based on an expected proportion of all neonatal deaths attributable to severe infection, and of those, attributable to a drug resistant infection to the first line treatment (Laxminarayan et al, 2016). Even with planned investment in laboratory capacity for microbiology, from the UK’s Fleming Fund, the US Centres for Disease Control and others, surveillance is unlikely to expand beyond a reference site model in most low resource settings (Seale et al, 2017), leaving population levels of AMR, and clinical impact of drug resistance relatively unknown. The scale of the AMR problem is inferred rather than known, even in relatively high resource settings.…”
Section: Stabilising Antimicrobial Resistance As a Threatmentioning
confidence: 99%